An empirical test of the interpersonal theory of suicide in a heterogeneous eating disorder sample. Issue 2 (17th November 2016) - Pisetsky, Emily M.; Crow, Scott J.; Peterson, Carol B.
ABSTRACT: Objective: The Interpersonal Theory of Suicide (IPTS) model has not been fully tested in a clinical eating disorder (ED) population. Method: Participants ( N  = 114) completed questionnaires assessing suicidal ideation (SI), suicide attempts (SA), and constructs of the IPTS. Logistic regressions determined whether thwarted belongingness and perceived burdensomeness were associated with lifetime SI. Among those who endorsed lifetime SI, logistic regressions were used to determine whether elements of the acquired capability for suicide (fearlessness about death and painful and provocative events) were associated with lifetime SA. Results: Sixty‐five participants (57.0%) had lifetime SI and 24 (21.1%) had lifetime SA. Thwarted belongingness ( P  <   0.001) and perceived burdensomeness ( P  < 0.01) were associated with lifetime SI. Painful and provocative events were associated with lifetime SA ( P  < 0.03). Discussion: The IPTS was partially supported. Targeting interpersonal variables may be important in treating and preventing suicidality. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:162–165)